Avaliação de desempenho dos Centros e Recondicionamentos de Computadores (CRCs) a luz das políticas públicas de inclusão digital - ALMEIDA, Nonato Ribeiro de (2014)
This research aims to evaluate the performance of the government program CRC - Computer Reconditioning Center in an enlarged view of digital inclusion, ie a vision that goes beyond simple donation and provision of computers to people in social exclusion, involving aspects such as infrastructure access, development of technical expertise and contribution to the full digital citizenship. The research was based on the application of 72 questionnaires to former students and students of the program and 3 questionnaire CRCs managers. The results emphasize that the program performs actions of digital inclusion in broader perspective with significant results in relation to the volume of refurbished computers and made available for access, volume of people served, competence development techniques to students and actions for full digital citizenship.